Commercial additives for sulfur control in FCC gasoline: overall analysis of their impact on LCO and gasoline - del Rio Cuevas, José Daniel (2013)
Experiments with a commercial equilibrium catalyst and mixtures with a commercial additive for sulphur reduction in gasoline were performed in a CREC Riser Simulator reactor to study the impact of three different proportions of the additive in the overall performance of FCC units. The experiments were performed under conditions similar to those of the industrial operation (510 ̊C, CAT/OIL 6.4). The reaction effluents were analyzed by on-line gas chromatography using two detectors simultaneously: FID for hydrocarbons and PFPD for sulfur compounds. The highest reduction of sulfur in gasoline (about 10%) without yield penalties was obtained with the smallest amount of additive (10 wt.%); however, the reduction of sulfur in LCO was the least. At higher amounts of additive (40 wt.%) the effectiveness in reducing sulfur in gasoline was lower, but the sulfur reduction in LCO was higher (about 5%). Reducing the gasoline endpoint obviously reduced sulfur not only in the cut, but also in LCO. This positive effect was improved when the gasoline was produced with catalyst–additive mixtures, though a penalty in gasoline yield was observed. If the endpoint reduction of gasoline is very severe, it did not generate a more significant reduction of sulfur in gasoline an LCO, even when additives were present.